Financial Management and Marketing Optimisation of BSF (Maggot) Cultivation for the Empowerment of Housewives: Optimalisasi Tata kelola Keuangan dan Pemasaran Budidaya Lalat BSF (Maggot) untuk pemberdayaan Ibu Rumah Tangga - Aida Nahar; Fatchur Rohman; Subadriyah Subadriyah; Ali Ali (CONSEN: Indonesian Journal of Community Services and Engagement, 2026)
The management of kitchen organic waste in densely populated areas, such as Mlatiharjo village in East Semarang, faces challenges including waste accumulation, unpleasant odors, and reliance on landfills, which entails high transportation costs. This community service program aims to enhance housewives’ ability to effectively manage the finance and marketing of black soldier fly (BSF) farming businesses to support household economic empowerment and community sustainability. A participatory-applied approach was implemented through outreach, technical training, and intensive mentoring on financial management and digital marketing. Monitoring and evaluation utilized a mixed-methods approach with a pre-post intervention design and observation. Evaluation results indicate that the success rate of training and mentoring in the areas of understanding financial conditions, managing financial transactions, utilizing financial applications, managing promotional content, and optimizing websites as marketing tools reached 70%-75%, which falls into the “fairly good” category